Failure in shear bands for granular materials: thermo-hydro-chemo-mechanical effects. Issue 2 (13th May 2013) - Sulem, J.; Veveakis, M.; Stefanou, I.
Abstract : The failure of geomaterials in localised shear bands is one of the most common features in geomechanics. Early studies have provided the necessary criteria for the conditions of localisation, inclination angle with respect to the loading axes and thickness of the shear bands, when loaded at room temperature. This work extends these criteria for the problem of simple shear of a chemically active granular cohesionless material at higher temperatures, where thermal or chemical pressurisation may set in and influence the response of the material. It is deduced that failure occurs at higher positive values of the hardening modulus as temperature increases, that the shear band thickness also depends on the chemical reaction characteristics and that micro-inertia due to grain translations and rotations introduce the necessary rate dependency to regularise the system.